2020
DOI: 10.1111/jfpp.14685
|View full text |Cite
|
Sign up to set email alerts
|

Technological and probiotic potential of autochthonous lactic acid bacteria from spontaneously fermented dromedary milk

Abstract: This work aimed to identify autochthonous lactic acid bacteria (LAB) from spontaneously fermented dromedary milk and explore their technological and probiotic properties in vitro. Analysis of the strains by 16S rDNA gene sequencing revealed four strains as Enterococcus faecalis, one strain as Enterococcus faecium, one strain as Lactococcus lactis, and four strains as Streptococcus pasteurianus. However, two strains (LEFS 42 and LEFS 55) showed a low 16S similarity (97.60% and 97.54%, respectively) with the typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Additionally, Mulaw et al (2019) reported that all the isolates of LAB they tested (E052, E031, T035, and K011) were resistant to kanamycin and streptomycin. Likewise, Oussaief et al (2020) also reported that all the examined strains were resistant to erythromycin and kanamycin, while only the strain LEFS 41 was resistant to ampicillin. The antibiotic resistance of nine probiotic strains; three L. bulgaricus and six Streptococcus thermophilus isolated from commercial yoghurt and cheese in Tianjin, China, was investigated by Wang et al (2019) who found that eight isolates were resistant to at least one antibiotic, and six isolates displayed multidrug resistance.…”
Section: Antibiotic Resistance Of Probiotic Bacteriamentioning
confidence: 84%
See 1 more Smart Citation
“…Additionally, Mulaw et al (2019) reported that all the isolates of LAB they tested (E052, E031, T035, and K011) were resistant to kanamycin and streptomycin. Likewise, Oussaief et al (2020) also reported that all the examined strains were resistant to erythromycin and kanamycin, while only the strain LEFS 41 was resistant to ampicillin. The antibiotic resistance of nine probiotic strains; three L. bulgaricus and six Streptococcus thermophilus isolated from commercial yoghurt and cheese in Tianjin, China, was investigated by Wang et al (2019) who found that eight isolates were resistant to at least one antibiotic, and six isolates displayed multidrug resistance.…”
Section: Antibiotic Resistance Of Probiotic Bacteriamentioning
confidence: 84%
“…Similar findings were also observed for L. lactis LEFS 29 and Streptococcus sp. LEFS (Oussaief et al, 2020), L. helveticus M92 (Beganović et al, 2013), and Bacillus subtilis CP350 (Kim et al, 2019).…”
Section: Proteolytic Activitiesmentioning
confidence: 99%